2011
DOI: 10.3892/ijmm.2011.713
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin reduces the apoptotic effect of etoposide via Akt activation and up-regulation of p21cip

Abstract: Abstract. Previous studies on the apoptotic effect of aspirin mainly focus on colorectal cancer and breast carcinoma. Few studies have been designed to explore the effect of aspirin on hepatocellular carcinoma. In the present study, we observed that aspirin caused G0/G1 phase cell cycle arrest and reduced etoposide induced caspase-3 activation in hepatocellular carcinoma G2 (HepG2) cells. Further investigation demonstrated that aspirin notably enhanced the activity of Akt and ERK1/2. Blocking the activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Inhibition of COX2, one of the targets of aspirin, reportedly inhibits PI3K/Akt kinase activity in epithelial ovarian cancer [ 33 ]. Consistent with the current study, Feng and collegues reported that aspirin could induce Akt and ERK1/2 phosphorylation in HepG2 cells [ 34 ]. Our current study demonstrates that activation of AMPK contributes to the induction of Akt phosphorylation by aspirin.…”
Section: Discussionsupporting
confidence: 92%
“…Inhibition of COX2, one of the targets of aspirin, reportedly inhibits PI3K/Akt kinase activity in epithelial ovarian cancer [ 33 ]. Consistent with the current study, Feng and collegues reported that aspirin could induce Akt and ERK1/2 phosphorylation in HepG2 cells [ 34 ]. Our current study demonstrates that activation of AMPK contributes to the induction of Akt phosphorylation by aspirin.…”
Section: Discussionsupporting
confidence: 92%